Tinjauan Etika tentang Konten Tiktok Codebluuu Mengenai Review Makanan Oseng Bang Madun - Rachmadi, Naufal Irsyad; Saputra F., Dhidiq Zainul; Hayqal W, Raden Mas Raihan (Universitas Muhammadiyah Magelang, 2024)
This research aims to reveal and identify forms of ethics in social media. This type of research uses a qualitative descriptive method because the problem formulation is an ethical review of TikTok Codebluuu content regarding Oseng Bang Madun food reviews. This research shows that Codebluuu violated ethical regulations on social media in reviewing its product Oseng Oseng Bang Madun. The content of the shared post, namely Codebluuu, in its content seems to belittle the product of oseng bang madun. We already know that when creating content, we should think more about the words we say and the actions in the content. It can be concluded that the content from Codebluuu has violated many ethics in social media.